Preparation method of grid-reinforced boron carbide bulletproof ceramic

By designing the grid structure in boron carbide ceramics and performing hot press sintering, the problems of degradation of hardness and density increase during toughening, as well as the problem of unfavorable performance of weak splicing boundary areas, boron carbide ceramics with hardness outside and toughness inside are achieved, and its resistance to multiple strikes is improved.

CN119874391APending Publication Date: 2025-04-25ANHUI SHUANGFENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109629.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During the toughening process, boron carbide ceramics have problems such as decreasing hardness and increasing density due to the addition of the second phase, and the structural design of bulletproof ceramics is unfavorable to performance due to the existence of weak splicing boundaries.

Method used

By designing the grid structure and hot pressing sintering, boron carbide ceramics with hard outside and tough inside are prepared. The metal mesh reacts in situ with the boron carbide powder to form a second phase with a high melting point, forming a second phase distributed in a grid, thereby improving the fracture toughness and protective performance of the ceramic.

Benefits of technology

The external hardness and inner toughness characteristics of boron carbide ceramics are realized, which improves its resistance to multiple hits, avoids the problems of decreasing hardness and increasing density, and reduces overall crushing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874391A_ABST
    Figure CN119874391A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of grid-enhanced boron carbide bulletproof ceramic, which comprises the following steps: firstly, carrying out ball-milling treatment on boron carbide powder to obtain powder with smaller particle size, and placing a dry metal net of which the surface oxide is removed through solution cleaning at a fixed position according to a sample design diagram; the characteristic that a metal net and boron carbide powder are subjected to an in-situ reaction to generate a high-melting-point second phase is utilized, and the second phase distributed in a latticed mode is prepared in boron carbide ceramic through hot pressing sintering; the toughening effect and the compression stress brought by the second phase and the constraint effect of the grid structure are utilized, so that the boron carbide ceramic with the characteristics of hard outside and tough inside is obtained. Compression stress is formed in the ceramic sintering body due to the existence of constraint of the second-phase grid structure, so that not only is tensile stress formed in the impact process resisted, but also the overall breaking phenomenon of the bulletproof ceramic in the impact process can be effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic preparation, in particular to a method for preparing grid-reinforced boron carbide bulletproof ceramics. Background Art

[0002] Boron carbide ceramic material has a low density (2.52g / cm 3 ), high hardness and elastic modulus, low thermal expansion coefficient, high acid and alkali resistance, and good neutron absorption ability, and are widely used in military industry, abrasives, chemical devices, nuclear industry and other fields. In the military field, boron carbide ceramics stand out among many bulletproof ceramic materials due to their high hardness and low density. It is a bulletproof ceramic material with excellent performance. However, boron carbide ceramics have low fracture toughness (2-3MPa·m 1 / 2 ), which has the fatal disadvantage of being easily broken as a whole, which seriously restricts its improvement in the performance of resisting multiple blows in the field of bulletproof ceramics. Titanium diboride is also a bulletproof ceramic material with good bulletproof performance. Its hardness is slightly lower than that of boron carbide, and its density is relatively high, but it has a relatively high fracture toughness (4-5MPa·m 1 / 2 ). Compared with pure boron carbide, adding a toughening second phase inside it helps to improve its fracture toughness. This is due to the beneficial effect of changing the fracture mode of the ceramic from the original transgranular fracture to the intergranular fracture. Introducing the toughening second phase into boron carbide will help improve the resistance of boron carbide ceramics to multiple impacts. Therefore, the sintering preparation of second-phase toughened boron carbide ceramics has become a hot topic of research at home and abroad in recent years. Small-sized splicing of boron carbide ceramics and increasing constraints can help improve the resistance to multiple impacts, but the influence of the weak splicing area on the overall protective performance must be considered. The study of the splicing and constraint structure on the performance of bullet-proof ceramics is of great significance to the improvement of bulletproof performance.

[0003] Therefore, adding a toughening second phase to boron carbide and improving the structural design is considered to be the most effective way to improve the resistance of bulletproof ceramics to multiple hits. So far, the types of boron carbide ceramics toughened by the second phase have been reported, such as oxide second phases (Al2O3, Y2O3, etc.), carbides (SiC, TiC, etc.), borides (TiB2, CrB2, etc.), metals (Ti, Cu, etc.), etc. Some of the added toughening second phases will react with boron carbide during the sintering process, such as adding Al2O3 may form Al5O6BO3 phase, such as adding metal Ti will react with B4C to form TiB2 and C. Other added toughening second phases will not react with boron carbide during the sintering process, but will maintain their original composition, such as added SiC. Although the addition of a toughening second phase can improve the fracture toughness of boron carbide ceramics, since boron carbide is the third hardest material in the world, the mechanical properties such as hardness of the second phase and its products are likely to be lower than those of boron carbide ceramics, which is not conducive to the overall mechanical properties. At the same time, since boron carbide itself has a relatively low density, which is also an important consideration for its bulletproof application, the addition of a large amount of toughening second phase will cause an increase in the overall density, which will also have an adverse effect on bulletproof applications. In addition, in recent years, related research on the splicing structure and constraint restrictions of bulletproof ceramics has also received widespread attention. Ceramics are prepared into different shapes to form different splicing. The splicing structure and constraint restrictions of the bulletproof ceramics reported above have improved the ceramics' resistance to multiple hits to a certain extent, but the splicing boundary has a weak area because it is not a whole structure. The existence of this weak area will cause the protective effect of this area to drop sharply. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] Therefore, the purpose of the present invention is to provide a method for preparing a grid-reinforced boron carbide bulletproof ceramic, which overcomes the problem that the hardness of the boron carbide ceramic decreases and the density increases due to the addition of a second phase during the toughening process, and the problem that the bulletproof ceramic is unfavorable to the performance due to the presence of a weak zone at the splicing boundary during structural design, and prepares a boron carbide ceramic that is hard on the outside and tough on the inside by hot pressing and sintering through a grid structure design, and the optimal solution for the density, fracture toughness and protective performance of the boron carbide bulletproof ceramic can be achieved by flexibly regulating the grid structure.

[0006] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0007] A method for preparing a grid-reinforced boron carbide bulletproof ceramic, comprising the following steps:

[0008] S1. Design the schematic diagram, surface size and thickness of the sample to be pressed, and calculate the raw material mass required for each part according to the schematic diagram and the density of boron carbide. Cut the metal mesh into the same surface size as the sample to be pressed, and then put the cut metal mesh into a 1mol / L solution for cleaning for 3-5min to remove the surface oxide, then wash it with deionized water 5 times, and then dry it in a vacuum drying oven at 80℃ for 10-12h;

[0009] S2, taking boron carbide powder, grinding beads and alcohol, mixing them, putting them into a high-energy ball mill, ball milling for 10-12 hours to grind the boron carbide raw material into a particle size of 600-800 nm, and then drying them in a vacuum drying oven at 80° C. for 18-24 hours;

[0010] S3, the metal mesh finally obtained in step S1 and the boron carbide powder finally obtained in step S2 are loaded into the mold layer by layer according to the design, each layer of powder needs to be pressed flat with a pressing head at a pressure of 10MPa, and then pressed into shape under a cold press at 60-80MPa to obtain a boron carbide-metal mesh blank;

[0011] S4. Take out the boron carbide-metal mesh blank finally obtained in step S3, put it into a graphite mold covered with graphite paper, and hot-press sinter it in an argon atmosphere. The sintering temperature is controlled to be 1800-2000° C., the holding time is 60-120 min, and the sintering pressure is 20-60 MPa to obtain a grid-structure toughened boron carbide composite ceramic.

[0012] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic described in the present invention, a method for preparing a grid-reinforced boron carbide bulletproof ceramic is characterized in that, in step S1, the sample schematic diagram includes the surface size, thickness, number of metal mesh layers, and position of the metal mesh of the sample.

[0013] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic according to the present invention, in step S1, the surface dimensions of the samples include samples of different sizes and shapes as well as flat samples and samples with different curvatures.

[0014] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic according to the present invention, in step S1, the metal mesh is a Ti mesh.

[0015] As a preferred embodiment of the method for preparing a mesh-reinforced boron carbide bulletproof ceramic according to the present invention, in step S1, the solution for cleaning the oxide film of the metal mesh is an acid solution or an alkaline solution.

[0016] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic according to the present invention, in step S3, when the boron carbide powder and the metal mesh are loaded into the mold layer by layer according to the design, each layer of powder is required to be pressed flat with a pressing head at a pressure of 10 MPa before subsequent operations are performed.

[0017] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic according to the present invention, in step S4, the heating to 1900-2000°C in an argon atmosphere is carried out according to a step-by-step heating method, and the heating rate is: 0-800°C heating rate is 10-15°C / minute, 800-1500°C heating rate is 7-8°C / minute, and the heating rate above 1500°C is 5°C / minute. During the cooling process, the cooling rate above 1500°C is 5°C / minute.

[0018] As a preferred embodiment of the method for preparing a grid-reinforced boron carbide bulletproof ceramic described in the present invention, in step S4, the heating and pressurizing process is pressurized according to a step-by-step pressurization method, firstly a pre-pressing pressure of 1 MPa is performed, and when the temperature is 0-300°C, the pressure of 1 MPa is maintained unchanged, and then when the temperature is increased from 300°C to 800°C, the pressure is gradually increased to the set pressure, and finally the pressure remains unchanged until the end of the insulation stage, and then the pressure gradually drops to 1 MPa in the process of cooling to 1500°C, and the subsequent pressure is gradually reduced to 0 MPa.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. First, the boron carbide powder is ball-milled into a powder with a smaller particle size, and the dry metal mesh that has been pickled to remove the surface oxide is placed in a fixed position according to the sample design schematic diagram. The metal mesh and the boron carbide powder react in situ to generate a high melting point second phase, and the second phase distributed in a grid shape is prepared inside the boron carbide ceramic by hot pressing and sintering; the toughening effect and compressive stress brought by the second phase and the constraint effect of the grid structure are utilized to obtain a boron carbide ceramic with external hardness and internal toughness. The boron carbide composite ceramic with a grid structure prepared by sintering has the characteristics of high surface hardness and high toughness in the core. At the same time, the compressive stress is formed inside the ceramic sintered body due to the existence of the second phase grid structure constraint, which not only resists the tensile stress formed during the impact process, but also can effectively reduce the overall crushing phenomenon of the bulletproof ceramic during the impact process. Therefore, the present invention provides a method for preparing a boron carbide composite ceramic that combines second phase toughening and structural constraint design, realizes the preparation of external hard and internal tough boron carbide bulletproof ceramics, improves the resistance to multiple strikes of bulletproof ceramics, and has broad application prospects.

[0021] 2. Titanium diboride is generated by the reaction between titanium and boron carbide, a metal mesh is added to the inside of the boron carbide, and hot pressing and sintering are used to prepare B4C composite ceramics with a grid structure TiB2 inside.

[0022] 3. Grid structure TiB2 is added inside B4C ceramics, making full use of the characteristics of titanium diboride toughening phase and structural constraints. On the one hand, the grid structure of titanium diboride toughening phase is added, rather than a large amount of mixed powder addition, which tries to avoid the adverse effects on density and hardness; on the other hand, the grid structure not only deflects cracks and improves fracture toughness, but also plays a restraining role, minimizing overall rupture and improving resistance to multiple impacts.

[0023] 4. The B4C-TiB2 composite ceramics prepared by this method have the effect of hard outside and tough inside, ensuring high surface hardness. The micron indentation hardness value is 30.1GPa. At the same time, the fracture toughness is significantly improved. The fracture toughness can reach 5-7MPa·m by using the three-point bending single-sided open beam method. 1 / 2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below in combination with the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 The present invention is a flow chart of a method for preparing a grid-reinforced boron carbide bulletproof ceramic. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0027] The invention provides a preparation method of a grid-reinforced boron carbide bulletproof ceramic, which overcomes the problem that the hardness of the boron carbide ceramic decreases and the density increases due to the addition of a second phase during the toughening process, and the problem that the performance of the bulletproof ceramic is unfavorable due to the existence of a weak area at a splicing boundary during structural design. Boron carbide ceramics that are hard on the outside and tough on the inside are prepared by hot pressing and sintering through grid structure design, and the optimal solution of the density, fracture toughness and protective performance of the boron carbide bulletproof ceramic can be achieved by flexibly regulating the grid structure.

[0028] S1. Design a schematic diagram of the sample to be pressed, with a diameter of 32mm and a thickness of 6mm, and lay a layer of metal mesh at a thickness of 3mm, and calculate the mass of boron carbide required for every 3mm thickness based on the schematic diagram and the density of boron carbide; cut a layer of metal mesh into the same surface size as the sample to be pressed; put the cut metal mesh into a 1mol / L hydrofluoric acid solution for pickling for 5min to remove surface oxides, then wash it with deionized water 5 times, and then dry it in a vacuum drying oven at 80℃ for 12h;

[0029] S2. Take a certain amount of boron carbide powder, grinding beads and alcohol (mass ratio 1:1:1.5), mix them, put them into a high-energy ball mill, and grind them for 10 hours to grind the boron carbide raw material into a particle size of 800nm; then dry it in a vacuum drying oven at 80℃ for 24 hours, and pass it through a 100-mesh sieve to prevent agglomeration;

[0030] S3, the metal mesh finally obtained in step S1 and the boron carbide powder finally obtained in step S2 are loaded into the mold layer by layer according to the design, first load the boron carbide powder required for 3mm thickness, followed by the metal mesh that has been pickled and dried, and then the boron carbide powder required for 3mm thickness, and each layer of powder needs to be pressed flat with a pressure head at a pressure of 10MPa. This helps to achieve uniform powder spreading and obtain consistent density, while making the position of the metal mesh more accurate in accordance with our design schematic, and then press-molding under a cold press at 60MPa to obtain a boron carbide-metal mesh blank;

[0031] S4. Take out the boron carbide-metal mesh blank finally obtained in step S3, put it into a graphite mold (diameter 32 mm) covered with graphite paper, and perform hot pressing sintering under argon atmosphere. The sintering temperature is controlled to be 2000°C, the holding time is 120 min, and the sintering pressure is 60 MPa. A boron carbide composite ceramic with a layer of grid structure toughening can be obtained, wherein the temperature is heated according to the step-by-step heating method, and the heating rate is: 0-800°C heating rate is 10-15°C / min, 800-1500°C heating rate is 7-8°C / min, 1500°C-2000°C heating rate is 5°C / min, during the cooling process, the cooling rate at 2000°C-1500°C is 5°C / min, and then cooled with the furnace. Sintering in an argon atmosphere prevents the formation of oxidation products. The heating and cooling rates from 1500℃ to 2000℃ are slow, all to prevent sintering too quickly and cracking. The heating and pressurizing process also follows the step-by-step pressurization method. First, pre-press 1MPa pressure is applied. When the temperature is 0-300℃, the pressure is kept constant at 1MPa. Then, when the temperature rises from 300℃ to 800℃, the pressure is gradually increased to the set pressure. Finally, the pressure remains unchanged until the end of the insulation stage. Then, the pressure gradually drops to 1MPa during the cooling process to 1500℃, and then the pressure gradually decreases to 0MPa. Applying pressure during the sintering process helps to promote the sintering process and obtain a higher density sample.

[0032] Wherein, the B4C powder is produced by Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of ≥99.9%, the metal mesh is produced by Shanghai Yousen Metal Materials Co., Ltd., with a purity of ≥99%, the hydrofluoric acid solution is produced by Sinopharm Chemical Reagent Co., Ltd., AR (Shanghai test), ≥40.0%, the alcohol is produced by Shanghai Titan Technology Co., Ltd., 68%-72%, RG, the ball milling process uses a high-energy ball mill, which is 01-HDDM type produced by Union Process Company of the United States, the grinding beads are SiC grinding balls produced by Haining Kewei Bearing Technology Co., Ltd., the vacuum drying oven is DZF-6050 type produced by Shanghai Yiheng Scientific Instrument Co., Ltd., the 100-mesh screen is a 304 stainless steel screen produced by Jiufeng Metal Wire Mesh Manufacturing Co., Ltd., the graphite mold is produced by Liaoyang Xingwang Graphite Products Co., Ltd., the hot pressing sintering furnace is a vacuum hot pressing sintering furnace produced by Shanghai Chenhua Technology Co., Ltd., and the argon is produced by Liquid Air (Shanghai) Compressed Gas Co., Ltd., with a purity of ≥99.99%.

[0033] Example 2

[0034] S1. Design a schematic diagram of the sample to be pressed, with a diameter of 32mm and a thickness of 6mm, and lay a layer of metal mesh at the position of the thickness of 2mm and 4mm, and calculate the mass of boron carbide required for every 2mm thickness according to the schematic diagram and the density of boron carbide; cut the two layers of metal mesh into the same surface size as the sample to be pressed; put the cut metal mesh into 1mol / L hydrofluoric acid solution for pickling for 5min to remove the surface oxide, then wash it with deionized water 5 times, and then dry it in a vacuum drying oven at 80℃ for 12h;

[0035] S2. Take a certain amount of boron carbide powder, grinding beads and alcohol (mass ratio 1:1:1.5), mix them, put them into a high-energy ball mill, and grind them for 10 hours to grind the boron carbide raw material into a particle size of 800nm; then dry it in a vacuum drying oven at 80℃ for 24 hours, and pass it through a 100-mesh sieve to prevent agglomeration;

[0036] S3, the metal mesh finally obtained in step S1 and the boron carbide powder finally obtained in step S2 are loaded into the mold layer by layer according to the design, first load the boron carbide powder required for 2mm thickness, followed by a layer of pickled and dried metal mesh, then the boron carbide powder required for 2mm thickness, then a layer of pickled and dried metal mesh, and then the boron carbide powder required for 2mm thickness, and each layer of powder needs to be pressed flat with a pressure head at a pressure of 10MPa. This helps to achieve uniform powder laying and obtain consistent density, while making the position of the metal mesh more accurate in accordance with our design schematic, and then press-molding under a 60MPa cold press to obtain a boron carbide-metal mesh blank;

[0037] S4. Take out the boron carbide-metal mesh blank finally obtained in step S3, put it into a graphite mold (diameter 32 mm) covered with graphite paper, and perform hot pressing sintering under argon atmosphere. The sintering temperature is controlled to be 2000°C, the holding time is 120min, and the sintering pressure is 60MPa. Then, a two-layer grid structure toughened boron carbide composite ceramic can be obtained. The temperature is heated according to the step-by-step heating method, and the heating rate is: 0-800°C heating rate is 10-15°C / min, 800-1500°C heating rate is 7-8°C / min, 1500°C-2000°C heating rate is 5°C / min, and during the cooling process, the cooling rate at 2000°C-1500°C is 5°C / min, and then cooled with the furnace. Sintering in an argon atmosphere prevents the formation of oxidation products. The heating and cooling rates from 1500℃ to 2000℃ are slow, all to prevent sintering too quickly and cracking. The heating and pressurizing process also follows the step-by-step pressurization method. First, pre-press 1MPa pressure is applied. When the temperature is 0-300℃, the pressure is kept constant at 1MPa. Then, when the temperature rises from 300℃ to 800℃, the pressure is gradually increased to the set pressure. Finally, the pressure remains unchanged until the end of the insulation stage. Then, the pressure gradually drops to 1MPa during the cooling process to 1500℃, and then the pressure gradually decreases to 0MPa. Applying pressure during the sintering process helps to promote the sintering process and obtain a higher density sample.

[0038] Wherein, the B4C powder is produced by Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of ≥99.9%, the metal mesh is produced by Shanghai Yousen Metal Materials Co., Ltd., with a purity of ≥99%, the hydrofluoric acid solution is produced by Sinopharm Chemical Reagent Co., Ltd., AR (Shanghai test), ≥40.0%, the alcohol is produced by Shanghai Titan Technology Co., Ltd., 68%-72%, RG, the ball milling process uses a high-energy ball mill, which is 01-HDDM type produced by Union Process Company of the United States, the grinding beads are SiC grinding balls produced by Haining Kewei Bearing Technology Co., Ltd., the vacuum drying oven is DZF-6050 type produced by Shanghai Yiheng Scientific Instrument Co., Ltd., the 100-mesh screen is a 304 stainless steel screen produced by Jiufeng Metal Wire Mesh Manufacturing Co., Ltd., the graphite mold is produced by Liaoyang Xingwang Graphite Products Co., Ltd., the hot pressing sintering furnace is a vacuum hot pressing sintering furnace produced by Shanghai Chenhua Technology Co., Ltd., and the argon is produced by Liquid Air (Shanghai) Compressed Gas Co., Ltd., with a purity of ≥99.99%.

[0039] Example 3

[0040] S1. Design a schematic diagram of the sample to be pressed, with a diameter of 32mm and a thickness of 6mm, and lay a layer of metal mesh at a thickness of 3mm, and calculate the mass of boron carbide required for every 3mm thickness based on the schematic diagram and the density of boron carbide; cut a layer of metal mesh into the same surface size as the sample to be pressed; put the cut metal mesh into a 1mol / L hydrofluoric acid solution for pickling for 5min to remove surface oxides, then wash it with deionized water 5 times, and then dry it in a vacuum drying oven at 80℃ for 12h;

[0041] S2. Take a certain amount of boron carbide powder, grinding beads and alcohol (mass ratio 1:1:1.5), mix them, put them into a high-energy ball mill, and grind them for 12 hours to grind the boron carbide raw material into a particle size of 600nm; then dry it in a vacuum drying oven at 80℃ for 24 hours, and pass it through a 100-mesh sieve to prevent agglomeration;

[0042] S3, the metal mesh finally obtained in step S1 and the boron carbide powder finally obtained in step S2 are loaded into the mold layer by layer according to the design, first load the boron carbide powder required for 3mm thickness, followed by the metal mesh that has been pickled and dried, and then the boron carbide powder required for 3mm thickness, and each layer of powder needs to be pressed flat with a pressure head at a pressure of 10MPa. This helps to achieve uniform powder spreading and obtain consistent density, while making the position of the metal mesh more accurate in accordance with our design schematic, and then press-molding under a cold press at 60MPa to obtain a boron carbide-metal mesh blank;

[0043] S4. Take out the boron carbide-metal mesh blank finally obtained in step S3, put it into a graphite mold (diameter 32 mm) covered with graphite paper, and perform hot pressing sintering under argon atmosphere. The sintering temperature is controlled to be 1900°C, the holding time is 90 min, and the sintering pressure is 50 MPa. A boron carbide composite ceramic with a layer of grid structure toughening can be obtained, wherein the temperature is heated according to the step-by-step heating method, and the heating rate is: 0-800°C heating rate is 10-15°C / min, 800-1500°C heating rate is 7-8°C / min, 1500°C-1900°C heating rate is 5°C / min, during the cooling process, the cooling rate at 1900°C-1500°C is 5°C / min, and then cooled with the furnace. Sintering in an argon atmosphere prevents the formation of oxidation products, and the heating and cooling rates from 1500℃ to 1900℃ are slow, all to prevent sintering too quickly and cracking; the heating and pressurizing process also follows the step-by-step pressurization method, first pre-pressing 1MPa pressure, and maintaining 1MPa pressure when the temperature is 0-300℃, then when the temperature rises from 300℃ to 800℃, the pressure gradually increases to the set pressure, and finally the pressure remains unchanged until the end of the insulation stage, and then the pressure gradually drops to 1MPa during the cooling process to 1500℃, and then the pressure gradually decreases to 0MPa. Applying pressure during the sintering process helps to promote the sintering process and obtain a higher density sample.

[0044] Wherein, the B4C powder is produced by Shanghai Aladdin Biochemical Technology Co., Ltd., with a purity of ≥99.9%, the metal mesh is produced by Shanghai Yousen Metal Materials Co., Ltd., with a purity of ≥99%, the hydrofluoric acid solution is produced by Sinopharm Chemical Reagent Co., Ltd., AR (Shanghai test), ≥40.0%, the alcohol is produced by Shanghai Titan Technology Co., Ltd., 68%-72%, RG, the ball milling process uses a high-energy ball mill, which is 01-HDDM type produced by Union Process Company of the United States, the grinding beads are SiC grinding balls produced by Haining Kewei Bearing Technology Co., Ltd., the vacuum drying oven is DZF-6050 type produced by Shanghai Yiheng Scientific Instrument Co., Ltd., the 100-mesh screen is a 304 stainless steel screen produced by Jiufeng Metal Wire Mesh Manufacturing Co., Ltd., the graphite mold is produced by Liaoyang Xingwang Graphite Products Co., Ltd., the hot pressing sintering furnace is a vacuum hot pressing sintering furnace produced by Shanghai Chenhua Technology Co., Ltd., and the argon is produced by Liquid Air (Shanghai) Compressed Gas Co., Ltd., with a purity of ≥99.99%.

[0045] Although the present invention has been described above with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a grid-reinforced boron carbide bulletproof ceramic, characterized in that: Here are the steps: S1. Design the schematic diagram, surface size and thickness of the sample to be pressed, and calculate the raw material mass required for each part according to the schematic diagram and the density of boron carbide. Cut the metal mesh into the same surface size as the sample to be pressed, and then put the cut metal mesh into a 1mol / L solution for cleaning for 3-5min to remove the surface oxide, then wash it with deionized water 5 times, and then dry it in a vacuum drying oven at 80℃ for 10-12h; S2, taking boron carbide powder, grinding beads and alcohol, mixing them, putting them into a high-energy ball mill, ball milling for 10-12 hours to grind the boron carbide raw material into a particle size of 600-800 nm, and then drying them in a vacuum drying oven at 80° C. for 18-24 hours; S3, the metal mesh finally obtained in step S1 and the boron carbide powder finally obtained in step S2 are loaded into the mold layer by layer according to the design, each layer of powder needs to be pressed flat with a pressing head at a pressure of 10MPa, and then pressed into shape under a cold press at 60-80MPa to obtain a boron carbide-metal mesh blank; S4. Take out the boron carbide-metal mesh blank finally obtained in step S3, put it into a graphite mold covered with graphite paper, and hot-press sinter it in an argon atmosphere. The sintering temperature is controlled to be 1800-2000° C., the holding time is 60-120 min, and the sintering pressure is 20-60 MPa to obtain a grid-structure toughened boron carbide composite ceramic.

2. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S1, the sample schematic diagram includes the surface size, thickness, number of metal mesh layers, and position of the metal mesh of the sample.

3. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S1, the surface dimensions of the samples include different sizes and different shapes as well as flat samples and samples with different curvatures.

4. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S1, the metal mesh is a Ti mesh.

5. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S1, the solution for cleaning the oxide film of the metal mesh is an acid solution or an alkaline solution.

6. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S3, when the boron carbide powder and the metal mesh are loaded into the mold layer by layer according to the design, each layer of powder is required to be pressed flat with a pressing head at a pressure of 10 MPa before subsequent operations are performed.

7. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S4, the heating to 1900-2000°C in an argon atmosphere is carried out according to a step-by-step heating method, and the heating rate is: 0-800°C heating rate is 10-15°C / minute, 800-1500°C heating rate is 7-8°C / minute, and the heating rate above 1500°C is 5°C / minute. During the cooling process, the cooling rate above 1500°C is 5°C / minute.

8. The method for preparing a grid-reinforced boron carbide bulletproof ceramic according to claim 1, characterized in that: In step S4, the heating and pressurizing process is pressurized according to the step-by-step pressurization method, first pre-pressing with a pressure of 1 MPa is performed, and the pressure of 1 MPa is maintained unchanged when the temperature is 0-300°C, and then when the temperature increases from 300°C to 800°C, the pressure is gradually increased to the set pressure, and finally the pressure remains unchanged until the end of the insulation stage, and then the pressure gradually drops to 1 MPa in the process of cooling to 1500°C, and the subsequent pressure gradually decreases to 0 MPa.